Elevational gradient and vegetation‐environmental relationships in the central Hyrcanian forests of northern Iran. (14th January 2016) - Moradi, Halime; Naqinezhad, Alireza; Siadati, Soudeh; Yousefi, Yadollah; Attar, Farideh; Etemad, Vahid; Reif, Albert
Abstract : Tertiary‐relict Hyrcanian (Caspian) forest along the shores of the southern Caspian Sea is a center of biodiversity. Still, there is little information on plant diversity patterns in this area. This study evaluated plant diversity, variation in life forms, and geographical distribution of the zonal vegetation types and their relationships with environmental variables, in the educational and experimental forest of Kheyrudkenar, an important protected area in the central Hyrcanian forest of northern Iran. For this purpose, 226 vegetation plots of 400 m 2 were laid out along two altitudinal transects from the lowlands (100 m a.s.l.) to the timberline (2000 m a.s.l.). Four vegetation types were identified using modified TWINSPAN, indirect and direct gradient analyses. Species‐related (species diversity indices, life form and phytogeographical elements) and environmental variables (climate, topographic and soil variables) were calculated and subjected to one‐way ANOVA among the vegetation types. Both constrained (CCA) and unconstrained (DCA) ordination analyses showed an almost identical variation of the floristic composition along their axes and demonstrated that there are two main gradients in the Hyrcanian forest. Elevation together with annual precipitation and mean annual temperature were the most important factors controlling the floristic composition in the area. Topographic features such as slope inclination and heat index were found to be important within an elevation zone/vegetation type. Soil physical and chemical properties were of secondary importance for the separation of the vegetation types. This knowledge will be useful for forest management and conservation practices in the Hyrcanian area with its distinct and unique flora and vegetation.